Xenotransplantation: history, problems and development prospects - V. A. Gulyaev; M. Sh. Khubutiya; M. S. Novruzbekov; A. S. Mironov; O. D. Olisov; K. N. Lutsyk; S. V. Zhuravel; K. M. Magomedov; R. B. Akhmetshin; B. I. Yaremin (Трансплантология (Москва), 2019)
The paper reviews the milestones and prerequisites in the history of the emergence and development of xenotransplantation. The currently existing barriers (immunological, infectious, genetic, ethical, and regulatory) to the development of this organ and tissue transplantation type have been studied. Available data on theoretical research and experimental studies have been reviewed. The prospects for performing xenotransplantation in various combination of species have been assessed. The forms and variants of the xenograft rejection reaction have been described. Genetic engineering approaches to overcoming xenoimmunological incompatibility are described. An assessment is made of ways to overcome existing barriers and prospects for the further development of xenotransplantation as a scientific section of transplantology.